LIPID PROFILE IN NON-OBESE AND NON-DIABETIC HYPERTENSIVE PATIENTS (Journal of Medical & Health Sciences Review, 2025)
Background: Hypertension is a strong predictor for cardiovascular morbidity and typically coexist with dyslipidemia. Hypertensive patients may also have dyslipidemia, which further increases their risk of atherosclerosis, independent of obesity or diabetes. The lipid profile in these patients is of valuable importance for differentiating the cardiovascular risk regardless of their concomitant metabolic syndromes.Objectives: This study aimed to evaluate the role of lipid profile (LP) abnormalities in non-obese, non-diabetic hypertensive patients and their impact on cardiovascular disease (CVD) risk beyond traditional risk factors. Study Design: This is a cross-sectional study.Place and Duration of study: From December 2024 to May 2025 in General Medicine Department, Bolan Medical Complex Hospital Quetta.Methods: One hundred non-diabetic, non-obese hypertensive subjects were included in a cross-sectional study. Fasting blood lipid profiles including total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) were detected. Data are expressed as mean ± standard deviation (SD). Statistical analysis was performed using SPSS version 24.0. Independent t-tests were applied, and p < 0.05 was considered statistically significant.Results: The study population had a mean age of 52.6 ± 9.4 years, with a male-to-female ratio of 1:1.2. A total of 100 hypertensive patients were enrolled. The mean lipid values were: total cholesterol (TC) 205.3 ± 34.7 mg/dL, LDL-C 132.8 ± 28.6 mg/dL, HDL-C 38.5 ± 6.9 mg/dL, and triglycerides (TG) 178.4 ± 41.2 mg/dL. There was Dyslipidemia in 62 Low HDL-C (p = 0.031) and high LDL-C (p = 0.042) were significantly associated with hypertension. These results indicate that there is a relatively high burden of lipid abnormality in hypertensive patients beyond obesity or diabetes.Conclusions: Non-obese non-diabetic hypertensive patients present dyslipidemia, mainly hyper-LDL-C and hypo-HDL-C, thus showing higher risk for cardiovascular disease. Hypertension in itself can be a potential risk factor for lipid abnormalities, stressing the importance of routine monitoring of lipids even without regular metabolic risk factors. It has been shown that early screening and treatment of dyslipidemia could effectively decrease future cardiovascular events in essential hypertensive patients.